PRAYER CROSSES-JORS OF THE BLACK SEA ADYGS-SHAPSUGS: BASED ON THE MATERIALS OF THE MAE RAS - Stybin, Vitalij Vladimirovic (History, Archeology and Ethnography of the Caucasus, 2024)
Research into the hybrid and syncretic cults of the Black Sea Adyghe-Shapsugs inevitably faces the issue of interpretation of the prayer crosses-jors as ritual elements of a bygone tradition. These crosses come in three forms: T-shaped, Y-shaped, and Byzantine-Caucasian Christian. The first and last types have been documented since at least the 18th century through travelers’ descriptions. The T-shaped variant, however, is only mentioned in texts, while almost all drawings depict Byzantine-Caucasian Christian crosses. Y-shaped crosses were identified by researchers in the 1930s during ethnographic expeditions. Initially, they were simplistically categorized as “pagan fetishes” due to the political context, leading to their neglect in museum storage and academic study for many years. A revised interpretation provides a fresh perspective on the prayer crosses-jors. This article explores various interpretations of their symbolism within the sacred narratives of folk Christianity, which have been preserved in the culture of the Black Sea Adyghe-Shapsugs. Additionally, the article offers a new interpretation of the well-known tapshi staff among the Circassians (Adyghe), which had been erroneously identified as a cross-jor. The author draws on samples of crosses-jors stored in the MAE RAS and photographs taken in 1939 by Evgeny Shilling and Sergey Tokarev in the Black Sea Shapsugia. These photographs are introduced into scientific circulation for the first time with the permission of the MAE RAS.
Keywords: ethnography; rituals; North Caucasus; Adyghe; Circassians; folk Christianity; jors; cross; history of the Caucasus; cultural anthropology